A Case of Acute Myocardial Infarction during Chemotherapy of Advanced Rectal Cancer - Kashiwagi, Yoshiyuki (Nurse Media Journal of Nursing, 2018)
Background: Cetuximab, irinotecan, levoforinate, and 5-FU (FOLFIRI) are medicines commonly administered to advanced colorectal cancer patients through chemotherapy. Although this regimen is standardized for recurrent metastatic colorectal cancer, the emerging of myocardial infarction is rare.Purpose: The purpose of this study was to consider the development of myocardial infarction during the chemotherapy of colorectal cancer.Methods: A retrospective case study was conducted to one patient. An 80-year-old man who developed acute myocardial infarction was in chemotherapy with cetuximab + FOLFIRI with multiple lung metastases after rectal cancer surgery. Data were collected from the patient’s medical and nursing records as well as the physiological function test results.Results: Three days after the 38th administration, the patient visited an emergency outpatient mainly with complaints of dyspnea and back pain. Electrocardiogram showed that the lower wall infarction was suspected. The patient was transferred to a specialized cardiovascular hospital. Emergency coronary angiography was performed in the diagnosis of acute myocardial infarction, and percutaneous coronary intervention was performed. The patient was discharged on the 10th of disease day.Conclusion: In this case, it was thought that cetuximab + FOLFIRI synergistically induced hyper thrombogenicity, coronary plaque erosion, and acute myocardial infarction. It may also be necessary for interventions such as monitoring the risks in daily living by the medical care providers and guidance on risk avoidance behaviors.